Vitamin and mineral supplementation and rate of gain during the first trimester of gestation affect concentrations of amino acids in maternal serum and allantoic fluid of beef heifers. (25th January 2021) - Menezes, Ana Clara B; McCarthy, Kacie L; Kassetas, Cierrah J; Baumgaertner, Friederike; Kirsch, James D; Dorsam, Sheri; Neville, Tammi L; Ward, Alison K; Borowicz, Pawel P; Reynolds, Lawrence P; Sedivec, Kevin K; Forcherio, J Chris; et al.
Abstract: The objective of this study was to evaluate the effects of feeding vitamin and mineral (VTM ) supplement and (or) rate of gain (GAIN) during early gestation on amino acid (AA ) concentrations in allantoic fluid (ALF ) and amniotic fluid (AMF ) and maternal serum. Seventy-two crossbred Angus heifers (initial BW = 359.5 ± 7.1 kg) were randomly assigned to one of four treatments in a 2 × 2 factorial arrangement with main effects of VTM supplement (VTM or NoVTM ) and rate of gain (GAIN ; low gain [LG ], 0.28 kg/d, vs. moderate gain [MG ], 0.79 kg/d). The VTM treatment (113 gheifer −1 d −1, provided macro and trace minerals and vitamins A, D, and E to meet 110% of the requirements specified by the NASEM in Nutrient requirements of beef cattle. Washington, DC: The National Academies Press. doi:10.17226/19014, 2016) was initiated 71 to 148 d before artificial insemination (AI ). To complete the factorial arrangement of treatments, at breeding heifers were either maintained on the basal diet (LG), or received MG diet which was implemented by adding a protein/energy supplement to the LG diet. Thirty-five gestating heifers with female fetuses were ovariohysterectomized on d 83 of gestation and maternal serum, ALF, and AMF were collected. Samples were analyzed for concentrations of neutral AA: Ala, Asn, Cys, Gln, Gly, Ile, Leu, Met, Phe, Pro, Ser, Thr, Trp, Tyr, and Val; cationic AA: Arg, His, and Lys; and anionic AA: Asp and Glu. In serum, a VTM × GAIN interaction ( P = 0.02) was observed for Glu, with greater concentrations for VTM-LG than VTM-MG. Concentrations of serum Cys, Met, and Trp were greater ( P ≤ 0.03) for MG than LG. In ALF, concentrations of Glu were affected by a VTM × GAIN interaction, where VTM-MG was greater ( P < 0.01) than all other treatments. Further, ALF from VTM had increased ( P ≤ 0.05) concentrations of His, Asp, and 12 of the 14 neutral AA; whereas GAIN affected concentrations of Arg, Cys, and Asp, with greater concentrations ( P ≤ 0.05) in MG heifers. In AMF, AA concentrations were not affected ( P ≥ 0.10) by VTM, GAIN, or their interaction. In conclusion, increased concentrations of AA in maternal serum and ALF of beef heifers were observed at d 83 of gestation in response to VTM supplementation and rate of gain of 0.79 kg/d, which raises important questions regarding the mechanisms responsible for AA uptake and balance between the maternal circulation and fetal fluid compartments.